Characterization of double humanized BLT-mice with stable engraftment of a human gut bacterial microbiome - Daharsh, Lance; Lohani, Saroj Chandra; Ramer-Tait, Amanda E.; Li, Qingsheng (Frontiers in Microbiomes, 2024)
Humanized mice with human-like immune systems are commonly used to study immune responses to human-specific pathogens. However, one limitation of using humanized mice is their native murine gut microbiota, which significantly differs from that in humans. Given the importance of the gut microbiome to human health, these differences may profoundly impact the ability to translate results from humanized mouse studies to humans. Further, there is a critical need for improved pre-clinical models to study the complex in vivo relationships of the gut microbiome, immune system, and human disease. We previously created double humanized mice with a functional human immune system and a stable, human-like gut microbiome. Here, we characterized the engrafted human gut bacterial microbiome in our double humanized mouse model generated by transplanting fecal material from healthy human donors into the gut of humanized mice. Analysis of bacterial microbiomes in fecal samples from double humanized mice revealed they had unique 16S rRNA gene profiles consistent with those of the individual human donor samples. Importantly, transplanted human-like gut microbiomes were stable in mice for the duration of the study, extending up to 14.5 weeks post-transplant. Microbiomes of double humanized mice also harbored predicted functional capacities that more closely resembled those of the human donors than humanized mice. In conclusion, our study highlights the successful engraftment of human fecal microbiota in BLT humanized mice and underscores the stability of this model, offering a valuable platform for investigating the intricate interplay among the human gut microbiome, immune system, and various diseases in vivo.